Indications and Outcomes of Uterine Artery Embolization in Patients with Uterine Leiomyomas - Hidenori Sasa; Tatsumi Kaji; Kenichi Furuya (Hindawi Limited, 2012)
Objective. To investigate the indication and limitations of uterine artery embolization (UAE), we retrospectively analyzed the case of patients with uterine leiomyomas who had undergone UAE. Methods. During the past 7 years, 25 patients with uterine leiomyomas had undergone UAE in our hospital. UAE was indicated in patients with menstrual disturbances such as hypermenorrhea or dysmenorrhea. The outcomes of this procedure for uterine leiomyomas were analyzed. Results. Improvement in the menstrual symptoms and/or reduction in the leiomyoma size after UAE were observed in 24 patients (96.0%). There was mean 67.9% reduction in the volume of leiomyomas at six months after UAE (𝑃<0.05). However, the symptoms recurred after UAE in 6 patients (24.0%), with multiple or intramural leiomyomas larger than 7 cm, which necessitated additional procedures. Conclusion. The indications and limitations of the UAE should be considered because of its noneffectiveness and/or recurrence in over 20% of patients with uterine leiomyomas.